Cold‐induced cutaneous vasoconstriction in humans: Function, dysfunction and the distinctly counterproductive. Issue 8 (16th May 2019) - Alba, Billie K.; Castellani, John W.; Charkoudian, Nisha
Abstract : New Findings: What is the topic of this review? This review presents an update and synthesis of normal mechanisms of human cutaneous vasoconstriction in response to cold stress. It then discusses conditions in which cutaneous vasoconstrictor responses are excessive or insufficient and cases in which cold‐induced vasoconstrictor responses become counter to maintaining thermal and haemodynamic homeostasis. What advances does it highlight? The review highlights our current understanding of the mechanisms that mediate alterations in cold‐induced cutaneous vasoconstriction in pathology and environmental extremes, which has important clinical implications for preventing cold‐ and cardiovascular‐related deaths. Abstract: In humans, cold‐induced peripheral vasoconstriction is an essential element of body temperature regulation. Given that the thermoregulatory system responds rapidly to changes in skin temperature, sympathetically mediated cutaneous vasoconstriction represents a crucial 'first line of defense' against excessive reduction in body temperature. Sympathetic noradrenergic vasoconstrictor nerves cause a rapid decrease in skin blood flow, thus increasing the insulative capacity of the skin and decreasing heat loss from the body. Small changes in the activity of these nerves are also responsible for the subtle changes in skin blood flow that occur with normal daily activities or minor changes in environmental temperature. With ageing, hypertension and other conditions, the cutaneous reflex vasoconstrictor response can become excessive or insufficient. Healthy older adults have impaired reflex vasoconstriction, which may result in an impaired ability to defend body temperature in some circumstances. Hypertension is associated with augmented vasoconstriction, which could have pathological implications for left ventricular afterload in individuals already at risk for cardiovascular events. Finally, in some cases, the reflex vasoconstrictor response becomes distinctly counterproductive to its own goals of maintaining cardiovascular and thermoregulatory homeostasis. Examples include Raynaud's phenomenon, in which exaggerated vasoconstriction can produce ischaemia in the periphery, and the cutaneous vasoconstrictor response to therapeutic body cooling in severe hyperthermia, which can limit the heat exchange necessary to prevent serious heat illness. Abstract :